From Wounds to Self-Worth: Understanding the Psychological Link Between Self-Esteem and Self-Harm Among Students - Rayhan Khairul Pratama; Yuda Syahputra; Dona Fitri Annisa; Azukaego Ifeoma Eluemuno; Rizki Akhri Juari (Asosiasi Asesmen Pendidikan (AAP), 2026)
Self-harming behavior has become an important mental health concern among adolescents and is frequently associated with various psychological factors, including self-esteem. This study aimed to examine the effect of self-esteem on self-harm among junior high school students and to identify its implications for school guidance and counseling services. A quantitative cross-sectional correlational design was employed involving 214 Grade VIII students from SMPN 14 Bekasi, Indonesia, who were selected using simple random sampling. Data were collected using researcher-developed self-esteem and self-harm questionnaires and analyzed using descriptive statistics and simple linear regression with IBM SPSS Statistics version 20. The findings revealed a significant negative effect of self-esteem on self-harm (β = -0.415, p < .001), indicating that students with higher self-esteem were less likely to engage in self-harming behavior. Self-esteem explained 31.6% of the variance in self-harm, suggesting that additional psychological and environmental factors may also contribute to adolescents' self-harming behavior. These findings highlight the protective role of self-esteem in reducing self-harm among adolescents and provide empirical support for the development of school-based counseling interventions that strengthen students' self-esteem and adaptive coping skills as part of preventive mental health programs.